Assessment of the effects of sulfate and nitrate on the temporal evolution of Klebsiella oxytoca and Staphylococcus aureus abundance under shaking conditions, in aquatic microcosm - Nola, Moïse; Nlep, Robert; Servais, Pierre; Kemka, Norbert; Zebaze Togouet,, Serge; Krier, François; Chihib, Nour-Eddine; Hornez, Jean-Pierre; Njine, Thomas (Revue des sciences de l'eau / Journal of Water Science, 2010)
Most chemicals in natural aquatic media can be assimilated by bacteria. The impact of various environmental conditions on this microbial process is not always clear. This study aimed at investigating changes in the abundance of Klebsiella oxytoca and Staphylococcus aureus under different shaking conditions, in aquatic microcosms containing nitrate and sulfate. Sodium chloride solution (8.5 g NaCl•L-1), and nitrate and sulfate solutions (0.005, 0.05, 0.5 and 5 g•L-1) containing bacteria were supplemented with tryptic peptone at a final concentration of 10 g•L-1. The solutions were incubated under shaking conditions (300, 350 and 400 rev•min-1). Bacteriological analyses were performed hourly over a 6-h period. During the first 3 h of incubation, results showed that the highest values of the apparent cell growth rates (CAGRs) with K2SO4 in pure cultures, at a shaking speed 400 rev•min-1, were 0.656 h-1 for S. aureus, and 0.364 h-1 for K. oxytoca. In mixed culture, the CAGR was 0.235 h-1 for S. aureus, and 0.388 h-1 for K. oxytoca, both recorded at 300 rev•min-1. With KNO3 in pure culture solutions, the CAGR was 0.353 h-1 for S. aureus at 300 rev•min-1, and 0.367 h-1 for K. oxytoca at 350 rev•min-1. In mixed culture it was 0.454 h-1 for S. aureus and 0.393 h-1 for K. oxytoca, both recorded at 350 rev•min-1. The highest value of the apparent cell inhibition rate (CAIR) for S. aureus was 0.520 h-1 in K2SO4 (5 g•L-1, 400 rev•min-1), and 0.115 h-1 in KNO3 (5 g•L-1, 300 rev•min-1). For K. oxytoca, it was 0.07 h-1 in K2SO4 in pure culture (0.05 g•L-1, 300 rev•min-1), and 0.044 h-1 in mixed culture (0.05 g•L-1, 350 rev•min-1). In KNO3 it was 0.239 h-1 in mixed culture (5 g•L-1, 300 rev•min-1). The growth and inhibition potentials of different microbial species were impacted by the chemical concentrations and the movement speeds.